2014
DOI: 10.3168/jds.2013-7573
|View full text |Cite
|
Sign up to set email alerts
|

Milk production during the colostral period is not related to the later lactational performance in dairy cows

Abstract: In dairy cows, milk yield increases rapidly after parturition until a peak at around wk 6 of lactation. However, the description of the shape of the lactation curve is commonly based on weekly average milk yields. For a more detailed analysis of the milk production curve from the very beginning of lactation including the colostral period and the effect of colostrum yield on further lactational performance, the first 10 milkings after parturition, daily milk yields from d 1 to 28 of lactation, and the cumulativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 26 publications
5
17
0
Order By: Relevance
“…The latter explanation may account for necrotic damage to mammary epithelium and could also result in independent epigenetic control of separate quarters. However, necrotic damage would lead to less productive parenchymal tissue and our previous work suggested that colostrum production was not related to parenchymal tissue mass (Baumrucker et al, 2010); a new report (Kessler et al, 2014) indicates no relationship between colostrum volume and subsequent milk volume within an animal. We had limited quarter disease information for the cows described in the current research and our sample size was too limiting; thus, no conclusion could be reached.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The latter explanation may account for necrotic damage to mammary epithelium and could also result in independent epigenetic control of separate quarters. However, necrotic damage would lead to less productive parenchymal tissue and our previous work suggested that colostrum production was not related to parenchymal tissue mass (Baumrucker et al, 2010); a new report (Kessler et al, 2014) indicates no relationship between colostrum volume and subsequent milk volume within an animal. We had limited quarter disease information for the cows described in the current research and our sample size was too limiting; thus, no conclusion could be reached.…”
Section: Discussionmentioning
confidence: 89%
“…A recent report by Kessler et al (2013) provides more evidence of the disconnect between mature milk secretion volume and colostrum volume. Furthermore, whereas concentration and mass of IgG 1 in first-milked colostrum are related (R 2 ~0.65; Baumrucker et al, 2010) within an animal, they can be significantly different.…”
Section: Discussionmentioning
confidence: 97%
“…The results of our milk yield and composition variables were consistent with other published results (Chamberlin et al, 2013;Hart et al, 2014;Kessel et al, 2008;Kessler et al, 2014;Rastani et al, 2005;De Vries and Veerkamp, 2000). Even with no observed significant effects of addition of any type of supplements used in this study on milk yield, the inclusion of supplements seems to be increase milk production in PP cows.…”
Section: Discussionsupporting
confidence: 92%
“…Dairy cows will produce anywhere from 1 to 20 kg of colostrum. Depending on parity, milk production will increase by approximately 10 kg in the first 5 days postpartum (Kessler et al 2014). With such a dramatic increase in milk production, enormous demands are exerted on body calcium reserves for transfer into milk.…”
Section: Introductionmentioning
confidence: 99%